EFEKTIVITAS âPNPM MANDIRI-RESPEKâ DI KABUPATEN JAYAPURA, PAPUA, TAHUN 2007-2010 - , Dorthea Renyaan; , Dr. Samodra Wibawa, M.Sc ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Poverty is a social problem that is, from time to time, found among the community, particularly in developing countries. In Indonesia poverty problem is a central issue. According to BPS (2010), during 2004-2010, in Indonesia the total and percentage of poor population in rural area tended to be greater compared to those in urban area. Poverty problem has also been encountered by those living in the villages or hinterlands of Papua. Hence, the Papua provincial government developed the Rencana Strategis Pembangunan Kampung (RESPEK)/ Kampung Development Strategic Plan program to cope with poverty problem. Such a program has been implemented since 2007 and in 2008 synchronization was arranged with national government, and it has been changed to be PNPM Mandiri-RESPEK (Program Nasional Pemberdayaan Masyarakat Mandiri-Rencana Strategis Pembangunan Kampung). This research was carried out in Waibu District and Namblong District of Jayapura Regency and it aimed to identify the effectiveness of this program. This was a qualitative research. Data were collected by using interview, observation, and documentation techniques. Informants involved the Head of Badan Pemberdayaan Masyarakat dan Pemerintahan Kampung (Community Empowerment Agency and Kampung Government of Jayapura Regency), District Head, Tim Pelaksana Kegiatan Kampung (TPKK)/Kampung Program Executive Team, Tim Pendamping Kampung, Distrik, Kabupaten (Kampung, District, and Regency Supporting Team), Head of Kampung, Tiga Tungku Team, and community members of Waibu District and Namblong District. Qualitative analysis technique using analysis process involving data reduction, data presentation, and conclusion drawing was utilized in this research. To test the validity of the information data triangulation technique was adopted. According to Barnard in Gibson (1990) concept of effectiveness used for the achievement of goals and targets agreed in the joint venture. Effectiveness is the measurement in terms of achievement of goals or objectives previously set. This means that if the targets or goals have been achieved as planned then the work was said to be effective. Result of the research on PNPM Mandiri-RESPEK program in Jayapura Regency showed that the program was effectively conducted. Output in terms of the potentials and capacities of the community in each decision making process had not been well run and the institutional capacity had been well performed. While the outcome of the development of participatory planning, public awareness of the village development, mutual confidence between the government and people of the community-owned institutions, management institutions belongs to the people in the village, and physical development are all going pretty well, although it is still a lack of public confidence in the actors PNPM Mandiri-RESPEK and government, lack of understanding of society and lack of supervision and cooperation of actors PNPM Mandiri-RESPEK. To this end, socialization through elucidation to community members in each kampung, training and supervision provided to PNPM Mandiri-RESPEK agents are necessary to perform in order to support their tasks and functions